Strategies for Preventing and Controlling Embezzlement in Indonesia through the Application of Situational Crime Prevention Approaches - Subadriyah (Journal of Business Crime, 2025)
Objective: This research aims to explore the potential application of Situational Crime Prevention (SCP) theory as a crime prevention approach that focuses on criminogenic situations, particularly in the context of embezzlement in Indonesia. Research Design & Methods: This research uses a descriptive qualitative approach with a literature review based on the TASP model to analyze patterns of embezzlement in public procurement in Indonesia. Prevention strategies were designed using the principles of Situational Crime Prevention (SCP) with a focus on controlling crime situations. Findings: This study found that the application of Situational Crime Prevention (SCP) theory can significantly reduce opportunities for corruption crimes, including embezzlement, in Indonesia. The crime script technique helps map the stages of embezzlement, enabling the identification and elimination of criminogenic opportunities. SCP is more effectively applied to small-scale corruption by low-level officials, where the integrity of oversight institutions is more secure, compared to large-scale corruption involving high-ranking officials. Implications: Implementing SCP emphasizes the importance of reducing opportunities for crime through technological surveillance, administrative transparency, and cross-disciplinary solutions before seeking socio-political structural reforms. Recommendations include strengthening electronic surveillance, transparent procurement systems, and ethics education for public officials to build a culture of accountability. Contribution: This study shifts the focus of criminology in Indonesia from individual perpetrators to crime opportunities as direct causes. The research offers a practical action-based approach, combining modern theory with technological and administrative solutions to minimize corruption, providing a foundation for the application of SCP in local contexts.